Load Characteristics of Tunnel Lining in Flooded Loess Strata considering Loess Structure - Yuyang Liu; Hongpeng Lai (Advances in Civil Engineering)
Loess has a unique structure and water sensitivity, and the immersion of loess leads to many tunnel lining problems in shallowly buried tunnels. Based on a tunnel in Gansu Province in China, two failure glide planes of a shallowly buried loess tunnel and their immersion modes are summarized. Finite element calculation of the structural Duncan-Chang constitutive model is realized via the secondary development of finite element software, by which the loads on the secondary lining are calculated and verified in comparison with measured results. The load characteristics of the secondary lining are studied. The load evolution is closely related to the immersion position and scope of the load. After the loess near the failure glide plane of the arch foot is flooded, the load on the arch foot sharply increases. As the immersion expands, the maximum load moves from the arch end up to the hance. After the loess near the failure glide plane of the hance is flooded, the load on the hance decreases slightly. The stability of the overlying loess decreases gradually, which causes the loads on the vault and arch shoulder to rapidly increase. Additionally, the load distribution characteristics on the secondary lining are summarized.